Western Music Learning Strategy Based on Microsoft Team and YouTube Media - Wijayanto, Heri; Sunarto, Sunarto; Ibnan Syarif, Moh. (Universitas Negeri Semarang, 2021)
The purpose of this study was to describe the strategy of learning western music based on Microsoft Team and YouTube Post-pandemic media in class XI of SMA N 1 Gubug, Grobogan Regency. The research method uses a qualitative approach with the type of case study research. The data in this study are descriptions of online western music learning strategies using Microsoft Team and YouTube obtained through interviews and observations as the main data and documentation as supporting data, with the research subjects being principals, music teachers and student representatives. After collecting data, qualitative data analysis was then carried out. The results of the study show that the learning of western music based on Microsoft Team and YouTube media has been carried out starting in the even semester of the 2020/2021 school year. The media was used by music teachers to provide post-pandemic western music materials. The media used is adjusted to the teaching material, namely in the form of displaying modules, videos, word files uploaded in Microsoft Teams. Music assessment carried out includes three aspects, namely the assessment of attitudes, knowledge and skills. Learning evaluation is carried out by the school every month, western music learning is carried out well from the participation, activeness and participation of students in participating in learning activities. The teacher becomes easier in delivering the material, the interaction between the teacher and students is more active. The effectiveness of western music learning for the criteria of teaching quality, suitability of the level of teaching, intensive learning is said to be effective. However, the criteria for the time required can be said to be ineffective.